Idiopathic duodenal varix presenting as a massive upper gastrointestinal bleeding: a case report - Nor Hanipah, Zubaidah; Jasmani, Asraf Haslam; Lee, Limi; Gee, Tikfu (Malaysian Medical Association, 2016)
Ectopic variceal bleeding is both a diagnostic dilemma and a therapeutic challenge, especially when it is located in the third part of the duodenum. Varix is rare in the absence of cirrhosis or portal hypertension. Because the diagnosis of this condition is usually delayed, treatment is administered late resulting in high morbidity and mortality rate. We report a case of a 61-year-old lady with an idiopathic duodenal varix presenting as an upper gastrointestinal bleeding.